2020
DOI: 10.3892/etm.2020.8943
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects bone biomechanical properties and microarchitecture in type�2 diabetic rats with osteoporosis via the TGFβ/Smad2/3 pathway

Abstract: Type 2 diabetic osteoporosis (T2DOP) has become a common secondary cause of osteoporosis that accelerates bone loss and leads to bone fractures. The aim of the current study was to investigate the association between the anti-osteoporotic effect of curcumin (Cur) and the transforming growth factor (TGF)β/Smads signaling pathway. Male Sprague-Dawley rats were used in the experiments. The type 2 diabetes mellitus (T2DM) animals were treated with Cur for 8 weeks and blood lipid markers, bone microstructure and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The mechanism of action in several molecular pathways is due to curcumin’s particular chemical structure, capable of having many molecular targets. The biological effects may include the inhibition of reactive oxygen species (ROS) production, playing a fundamental role, particularly for diseases related to oxidative stress and inflammation, such as DM ( 67 , 68 ). Figure 3 shows some systemic effects of curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action in several molecular pathways is due to curcumin’s particular chemical structure, capable of having many molecular targets. The biological effects may include the inhibition of reactive oxygen species (ROS) production, playing a fundamental role, particularly for diseases related to oxidative stress and inflammation, such as DM ( 67 , 68 ). Figure 3 shows some systemic effects of curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…As an antioxidant, curcumin can reduce oxidative stress, protect cells from oxidative stress damage, and play an active role in preventing and treating arthritis [ 24 ]. Another research evaluated the role of curcumin in osteogenesis, which showed that curcumin could reduce bone resorption in osteoporotic rats [ 25 ]. In the present study, we found that curcumin could inhibit inflammation response in MH7A and primary RA-FLSs by reducing TNF-α, IL-6, and IL-17 levels.…”
Section: Discussionmentioning
confidence: 99%
“…We found that mRNA expression of FUT8 was significantly downregulated in response to high-dose dexamethasone stimulation, along with significantly suppressed cell proliferation and osteogenic differentiation, suggesting that high-dose dexamethasone suppresses osteogenesis possibly by downregulating FUT8-mediated core fucosylation of osteogenesis-related glycoproteins. The canonical TGF-β pathway facilitates bone formation ( Baffi, Moran & Serra, 2006 ; Liang et al, 2020 ; Peters, Wang & Serra, 2017 ; Wang et al, 2013 ). Of note, FUT8-mediated core fucosylation is essential for TGF-β binding to TGFBRs ( Schachter, 2005 ; Van Staa, Leufkens & Cooper, 2002 ), and TGF-β/TGFBRs/Smads signaling is inhibited in glucocorticoid-induced osteoporosis and osteonecrosis ( Li et al, 2017 ; Tao et al, 2017 ; Xie, Hu & Shi, 2018 ).…”
Section: Discussionmentioning
confidence: 99%